Association Between Alcohol Consumption and Periodontal Pocket Formation - Arina Shafia (Al Makki Health Informatics Journal, 2025)
Background: Periodontal disease is one of the most prevalent chronic diseases affecting the oral cavity worldwide. Various risk factors contribute to the development of periodontal disease, one of which is alcohol consumption. Excessive alcohol intake is widely recognized as a major public health problem and has been associated with systemic conditions such as liver disease, cardiovascular disorders, and behavioral and mental health problems. Alcohol abuse has also been reported to impair host immune responses by reducing neutrophil, macrophage, and T-cell function, thereby increasing susceptibility to infection. Consequently, alcohol consumption may contribute to the development of periodontal pockets.Objective: This literature review aimed to summarize current evidence regarding the association between alcohol consumption and the risk of periodontal pocket formation.Methods: A narrative literature review was conducted by searching the PubMed, Scopus, and Google Scholar databases for peer-reviewed articles published between 2008 and 2025. The search combined the terms “alcohol consumption,” “periodontal pocket,” “periodontitis,” and “clinical attachment loss.” Observational, longitudinal, cohort, and cross-sectional studies, as well as systematic reviews and meta-analyses, were included, and their findings were synthesized descriptively.Results: Seven primary clinical studies were examined, together with supporting mechanistic and review evidence. Two studies reported no consistent association between light-to-moderate alcohol consumption and periodontal pocket development, whereas five reported that heavy or long-term alcohol consumption was associated with increased periodontal pocket depth and clinical attachment loss, most notably among heavy drinkers and smokers.Conclusion: This review demonstrates that excessive alcohol consumption is associated with periodontitis-related clinical manifestations, including periodontal pocket formation and clinical attachment loss.